AN EMPIRICAL EXAMINATION OF THE IMPACTS OF FINANCIAL LITERACY, FINANCIAL ANXIETY, AND LOSS AVERSION ON INVESTMENT DECISION, WITH SELF- EFFICACY AS A MODERATING FACTOR - Aprilia, Nabila Eka Nur; Putri Prawitasari, Putu (Sekolah tinggi ilmu ekonomi pemuda, 2025)
This study examines how financial knowledge, worries about money, and the fear of losing money influence the way people choose to invest. It also looks at self-efficacy, which is the belief in one’s own abilities, and how it affects these relationships. The research involved 100 regular investors in Bali and used a quantitative approach where data was collected through surveys. The data was analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that having good financial knowledge helps people make more informed and better investment choices. However, higher levels of money worries make people less confident and less likely to invest. The tendency to feel the pain of losing more than the joy of gaining, known as loss aversion, also has a negative effect on investment decisions. Self-efficacy influences how these factors affect investment choices. It strengthens the positive impact of financial knowledge and reduces the negative effects of money worries and loss aversion. These findings suggest that psychological and cognitive factors play an important role in helping retail investors make thoughtful decisions, especially for younger investors like those in Generation Z in Indonesia. Keywords: Financial Literacy, Financial Anxiety, Loss Aversion, Self-Efficacy, Investment Decision